Dynamics of Toxic Work Environments and Job Satisfaction: Analyzing the Mediating Role of Self-Efficacy and the Moderation of Social Support - Mariano Firmansyah; David Manafe; Septiani Arbania (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
This study aims to analyze in depth the influence of toxic work environments on employee job satisfaction in Kupang City, examining the role of self-efficacy as a mediating variable and social support as a moderating variable. While unhealthy work environments are often regarded as a primary factor in declining morale, this research explores the underlying psychological mechanisms behind such impacts. Employing a quantitative approach, data were collected via questionnaires from employees in Kupang City and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to test the structural relationships between variables.The results indicate that social support is a strong predictor that positively influences job satisfaction. Conversely, toxic work environments are confirmed to have a general negative impact on job satisfaction. However, a unique finding reveals that a toxic work environment actually enhances employee self-efficacy. Furthermore, self-efficacy is proven to act as a mediator that bridges the relationship between a toxic work environment and job satisfaction.Nonetheless, moderation testing demonstrates that social support is unable to weaken the negative influence of a toxic work environment on job satisfaction. This finding emphasizes that emotional support among colleagues has limitations in mitigating the effects of a destructive organizational culture. Therefore, systemic interventions to improve management and organizational culture are far more crucial than merely relying on internal social relations.